2017
DOI: 10.1155/2017/3578075
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of Adherence and Possible Solutions to Nonadherence to Antidiabetic Therapy in Women with Diabetes in Pregnancy: Patients’ Perspective

Abstract: Diabetes in pregnancy contributes to maternal mortality and morbidity though it receives little attention in developing countries. The purpose of the study was to explore the barriers to adherence and possible solutions to nonadherence to antidiabetic therapy in women with diabetes in pregnancy. Antidiabetic therapy referred to diet, physical activity, and medications. Four focus group discussions (FGDs), each with 7 participants, were held at a central hospital in Zimbabwe. Included were women with a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 35 publications
(44 reference statements)
3
38
0
2
Order By: Relevance
“…A US study among low-income mothers found that women who had diabetes in pregnancy (known diabetes and GDM) had nearly twice the risk of being diagnosed with depression during pregnancy or in the first year postpartum [41]. In our study, insulin administration, managing comorbidities and coping with other life stressors in addition to GDM were common sources of maternal distress associated with GDM, which have also been cited in other studies [37,38,42]. Having GDM was particularly burdensome for primigravidae women who felt 'robbed' of the joy of pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…A US study among low-income mothers found that women who had diabetes in pregnancy (known diabetes and GDM) had nearly twice the risk of being diagnosed with depression during pregnancy or in the first year postpartum [41]. In our study, insulin administration, managing comorbidities and coping with other life stressors in addition to GDM were common sources of maternal distress associated with GDM, which have also been cited in other studies [37,38,42]. Having GDM was particularly burdensome for primigravidae women who felt 'robbed' of the joy of pregnancy.…”
Section: Discussionsupporting
confidence: 81%
“…Further barriers relate to distance to health facility; perceptions of female body size and weight gain/loss related to pregnancy; practices related to a pregnant women's diet; societal negligence of women's health; lack of decision‐making power among women regarding their own health; the role of women in society and expectations that the pregnant woman move to her maternal home for delivery; and lack of adherence to recommended postpartum screening and low continued lifestyle modifications (, & Stray‐Pederson, 2; Nielsen, Courten, & Kapur, ; Nielsen, Kapur, Damm, Courten, & Bygbjerg, ). Additionally, a recent delivery experience, baby's health issues, personal and family adjustment to the new baby, a negative experience of medical care and services and concerns about postpartum and future health (as in, for example, fear of being informed that they have diabetes) were specifically related to the barriers to postpartum follow‐up care (Bennett et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The stages of thematic analysis followed were data organization, familiarization, transcription, coding, developing a thematic framework (searching for themes, reviewing, defining and naming them), indexing, displaying and reporting (interrelating and description of themes). Findings from the focus group discussions have already been published [13].…”
Section: Qualitative Phasementioning
confidence: 99%